Quantitative Analysis of Socio-Economic Status of Artisans of Wood Carving Industry of Saharanpur (Uttar Pradesh) - Dubey, Poonam; Singh, S. P.; Singh, Vertika; Mishra, Pradeep; Ray, Soumik; Williams, A. J. (Indian Forester, 2023)
The present study is focused on the socio-economic status of the artisans engaged in the wood carving handicraft industry of Saharanpur (U.P.) India. The study revealed that 99.42% of artisans are engaged with the wood carving industry. Out of these, 97.10% of artisans were doing hand carving work mainly on shisham. Illiteracy is the main issue behind the poor economic status of artisans. Overall, 66.95% of artisans were having very poor socio-economic status 56.23% of artisans were having annual income between 1-1.5 lakh. Due to low wages, only 50.75% of artisans wanted to pass their traditional knowledge of wood carving to their next generation. This study revealed the dark side of this world-famous wood carving industry of Saharanpur (U.P.) India.